Conceptualizing the impact of Strategic Capabilities on International Performance: Challenges and Opportunities presented by COVID-19 pandemic - Mohammad FALAHAT; Hon–Choong CHIN; Mui-Yin CHIN; Lee-Peng FOO (Communications of International Proceedings, 2021)
This paper proposes a conceptual model that highlights the critical impact of strategic capabilities on the competitive advantage and superior performance of SMEs in international markets. The critical role of COVID-19 as an external factor suggested that imposes challenges and opportunity for SMEs. Learning orientation, product development, pricing strategy, and marketing give SMEs strategic capabilities that lead to a competitive advantage. It was proposed further that price, product, and customer services are vital determinants of SMEs’ superior performance in the international markets. Also, the role of Digital Free Trade Zone as a facilitator to assist SMEs to further boost their competitive advantage in international markets has been highlighted.
Keywords: Strategic capabilities; competitive advantage; international performance; SMEs; COVID-19.